Innovation Strategy Implementation of Character Education for the Young Generation of Indonesia: Inovasi Strategi Implementasi Pendidikan Karakter Bagi Generasi Muda Indonesia - Katni, Katni (Universitas Muhammadiyah Sidoarjo, 2024)
The discourse of scholars in the field of education is that educational institutions are strategic for carrying out the transformation of values ​​and science, technology and art. This is how strategic educational institutions are as places for the transformation of values, knowledge, technology and art, so that in order to internalize and develop good character, it cannot be separated from the role of education in informal, formal and non-formal education channels. This research aims to analyze and discover the concept of implementing character education, character education strategies and values ​​implemented in character education. The results of this research show that the implementation of character education can be carried out through three stages of knowing the good, feeling the good and acting the good. Character education strategies can be integrated between micro, meso and macro level education. Character education is important for humans, so the role of educational institutions must not just provide insight into character, but also train, familiarize students with positive character over a long period of time so that it crystallizes in humans. The various character education values ​​developed in Indonesia are taken from 4 sources, namely: religion, Pancasila, culture and national education goals. Keywords: Educational Character, Educational Strategies, Sources of Character Values